2021
DOI: 10.1002/anie.202100551
|View full text |Cite
|
Sign up to set email alerts
|

Allostery‐Mimicking Self‐assembly of Helical Poly(phenylacetylene) Block Copolymers and the Chirality Transfer

Abstract: Allostery can regulate protein self‐assembly which further affects biological activities, and achieving precise control over the chiral suprastructures during self‐assembly remains challenging. Herein, to mimic the allosterical nature of proteins, the poly(phenylacetylene) block copolymers PPA‐b‐PsmNap with the dynamic helical backbone were synthesized to investigate their conformational‐transition‐induced self‐assembly. As the helical conformation of the block PsmNap spontaneously transforms from cis‐transiod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
52
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 46 publications
0
52
0
Order By: Relevance
“…As shown in Figure 4, Tables S3 and S4, and Figure S11, unimolecular spherical micelles were obtained in DPD simulations after minimizing the total free energy. Additionally, simulation results also showed that the diameters of unimolecular spherical micelles formed by solution self-assembly of poly(APOSS-BPOSS) 12 , poly(APOSS-BPOSS) 17 , poly(APOSS-BPOSS) 22 , and poly-(APOSS-BPOSS) 35 were 3.25, 3.58, 4.44, and 5.02 nm, respectively. Considering the inevitable errors of the coarse-grained (CG) model and experimental errors, the micellar sizes obtained by simulations were consistent with the experimental results measured by DLS (3.4, 3.6, 3.7, and 4.5 nm for n = 12, 17, 22, and 35, respectively).…”
mentioning
confidence: 89%
See 3 more Smart Citations
“…As shown in Figure 4, Tables S3 and S4, and Figure S11, unimolecular spherical micelles were obtained in DPD simulations after minimizing the total free energy. Additionally, simulation results also showed that the diameters of unimolecular spherical micelles formed by solution self-assembly of poly(APOSS-BPOSS) 12 , poly(APOSS-BPOSS) 17 , poly(APOSS-BPOSS) 22 , and poly-(APOSS-BPOSS) 35 were 3.25, 3.58, 4.44, and 5.02 nm, respectively. Considering the inevitable errors of the coarse-grained (CG) model and experimental errors, the micellar sizes obtained by simulations were consistent with the experimental results measured by DLS (3.4, 3.6, 3.7, and 4.5 nm for n = 12, 17, 22, and 35, respectively).…”
mentioning
confidence: 89%
“…The successful deprotection of the tert-butyl group was verified by 1 H NMR data. For example, in the 1 H NMR spectrum of poly(APOSS-BPOSS) 12 (Figure 1a, black curve), signals of protons in the tert-butyl group at δ 1.47 ppm (peak c) completely disappeared, while signals of protons in carboxyl groups at δ 4.57 ppm (peak e) appeared (the residue signals around 1.50 ppm were denoted to inevitable water). Then, we explored the self-assembly behaviors of poly-(APOSS-BPOSS) n in solution.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the erasing/inversion of morphological chirality by manipulating the stimuli-responsive conformational chirality of BCPs* not only proved the strong relationships between conformational and morphological chirality, but it also represented a novel methodology on morphological control. [128]…”
Section: Self-assembly Of Bcps* In Selective Solventsmentioning
confidence: 99%